Terapi Komplementer untuk Mengurangi Kecemasan pada Pasien yang Dilakukan Angiografi Koroner: A Literature Review - Neli Mariani; Elly Nurachmah; Agung Waluyo (FORIKES, 2021)
Coronary angiography is one of the most frequently performed clinical investigation and is still the main standard or “gold standard” in diagnosing the anatomical coronary arteries. Anxiety can arise in the patient who is going to be performed the procedure. It was found that 63,9 % experienced severe anxiety before the procedure was carried out. The purpose of this literature review is to determine the effect of complementary therapies on reducing anxiety in patients undergoing coronary angiography. This research is a secondary research type of literature review. Search for journal articles is done by accessing several databases, namely, Clinical keys, Scopus, Proquest, Pubmed, Google Scholar, Sciencedirect. In the last 5 years (2015-2020), searches used Indonesian and English. Keywords used include complementary therapy/ terapi komplementer, anxiety/ cemas, coronary angiography/cardiac catheterization/ Percutaneous Intervention/ kateterisasai jantung/angiografi jantung, guided imagery, aromatherapy/aromaterapi, massage therapy/terapi pijat, music therapy/ terapi musik, and Benson therapy”. There were a total of 2864 articles in total. After screening, 14 asrticles were found (2 articles in Indonesian and 12 articles in English). The review involve; 2 articles on Benson therapy, 1 article on guided imagery, 3 articles on aromatherapy, 3 articles on spiritual healing chants of the Quran, and 5 articles on massage. These articles can be used as one alternative of complementary therapies to reduce anxiety in patients undergoing coronary angiography.Keywords: complementary therapy; anxiety; cardiacABSTRAKAngiografi koroner merupakan salah satu pemeriksaan penunjang klinis yang paling sering dilakukan dan masih menjadi standar utama atau “gold standard” dalam mendiagnosis anatomis arteri koroner. Kecemasan dapat timbul pada pasien yang akan dilakukan tindakan tersebut. Didapatkan sebanyak 63,9 % mengalami kecemasan yang berat sebelum prosedur tindakan dilakukan. Tujuan literature review ini untuk mengetahui pengaruh terapi komplementer terhadap penurunan kecemasan pada pasien yang akan dilakukan tindakan angiografi koroner. Penelitian ini berupa penelitian sekunder jenis literature review. Pencarian jurnal artikel dilakukan dengan mengakses dari beberapa database yaitu, Clinicalkey, Scopus, Proquest, Pubmed, Google Scholar, Science direct. Dalam rentang waktu 5 tahun terakhir (2015-2020), pencarian menggunakan bahasa Indonesia dan bahasa Inggris. Kata kunci yang digunakan meliputi “complementary therapy/ terapi komplemeter, anxiety/kecemasan, coronary angiography/ cardiac catheterization/percutaneous intervention, guided imagery, aromatherapy/aromaterapi, massage therapy/terapi pijat, music therapy/terapi musik, dan benson therapy/ terapi Benson”. Ditemukan sebanyak 2864 artikel total keseluruhannya, setelah dilakukan penyaringan didapatkan 14 artikel (2 artikel berbahasa Indonesia dan 12 artikel berbahasa Inggris). Review yang dilakukan meliputi; 2 artikel mengenai terapi Benson, 1 artikel tentang guided imagery therapy, 3 artikel tentang aromaterapi, 3 artikel tentang terapi spiritual lantunan ayat Al Quran, dan 5 artikel tentang terapi pijat. Kesemua artikel ini dapat dijadikan sebagai alternatif untuk terapi komplementer dalam menurunkan kecemasan pada pasien yang akan dilakukan tindakan angiografi koronerKata kunci: terapi komplementer; cemas; angiografi jantung